2006
DOI: 10.4049/jimmunol.177.10.7203
|View full text |Cite
|
Sign up to set email alerts
|

Bruton’s Tyrosine Kinase Is Required for TLR-Induced IL-10 Production

Abstract: Bruton’s tyrosine kinase (Btk) is a critical signaling mediator downstream of the B cell Ag receptor. X-linked agammaglobulinemia is caused by mutations in Btk resulting in multiple defects in B cell development and function, and recurrent bacterial infections. Recent evidence has also supported a role for Btk in TLR signaling. We demonstrate that Btk is activated by TLR4 in primary macrophages and is required for normal TLR-induced IL-10 production in multiple macrophage populations. Btk-deficient bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
70
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 45 publications
10
70
1
2
Order By: Relevance
“…These observations correspond with earlier reports indicating that Btk plays a key role in macrophage stimulation by various TLRs (25). As an example, Btk has previously been demonstrated to be involved in TLR-dependent induction of pro-and anti-inflammatory cytokines (27,29). Moreover, Btk has been shown to mediate TLR8-and TLR9-dependent signaling in the human macrophage cell line THP-1 (47).…”
Section: Btk-mediated Ho-1 Induction By Lps Is Regulated Via the Transupporting
confidence: 78%
See 1 more Smart Citation
“…These observations correspond with earlier reports indicating that Btk plays a key role in macrophage stimulation by various TLRs (25). As an example, Btk has previously been demonstrated to be involved in TLR-dependent induction of pro-and anti-inflammatory cytokines (27,29). Moreover, Btk has been shown to mediate TLR8-and TLR9-dependent signaling in the human macrophage cell line THP-1 (47).…”
Section: Btk-mediated Ho-1 Induction By Lps Is Regulated Via the Transupporting
confidence: 78%
“…Because the Tec family kinase Btk has previously been shown to modulate gene expression in LPS-stimulated myeloid/macrophage cells (26,29) (for a review, see Ref. 25), we determined the effect of the specific pharmacological Btk inhibitor LFM-A13 on LPS-dependent HO-1 induction in the mouse macrophage cell line RAW264.7.…”
Section: Lps-dependent Ho-1 Gene Induction Is Blocked By the Specificmentioning
confidence: 99%
“…To understand further the mechanism by which the activation of TLR signaling in macrophages promoted tumor cell phagocytosis, we treated macrophages by combining TLR agonists with various inhibitors targeting key molecules that positively (MAPK, Btk) (23)(24)(25)(26)(27) or negatively (PI3K, caspase-1) (28,29) regulate TLR signaling. Blockers of MAPK, PI3K, and caspase-1 showed no effect on phagocytosis of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of Btk was also found to be required for the TLR2-induced expression of TNF-␣ and IL-1␤ in primary human monocytes/macrophages (21,22). Btk is implicated in TLR-induced IL-10 production (23). But the findings of Horwood et al (22) revealed an unexpected level of complexity insofar as they showed that in primary human macrophages Btk is not required for TLR2-and TLR4-induced IL-6 and IL-8 release from X-linked agammaglobulinemia PBMC stimulated with LPS.…”
Section: Figurementioning
confidence: 99%